Translational Control by Heme-Regulated eIF2α Kinase during Erythropoiesis - Chen, Jane-Jane (2014)
PURPOSE OF REVIEW: This review will provide an overview of the translational regulation of globin mRNAs and integrated stress response during erythropoiesis by heme-regulated eIF2α kinase (HRI). HRI is an intracellular heme sensor that coordinates heme and globin synthesis in erythropoiesis by inhibiting protein synthesis of globins and heme biosynthetic enzymes during heme deficiency. RECENT FINDINGS: It has been demonstrated recently that HRI also activates the eIF2αP-ATF4 integrated stress response in primary erythroid precursors to combat oxidative stress. During chronic iron/heme deficiency in vivo, this HRI-eIF2αP-ATF4 signaling is necessary both to reduce oxidative stress and to promote erythroid differentiation. Augmenting eIF2αP signaling by the small molecule salubrinal, which inhibits dephosphorylation of eIF2αP, reduces excess α-globin synthesis and induces translation of ATF4 mRNA in mouse β-thalassemic erythroid precursors. Intriguingly, salubrinal treatment of differentiating human CD34(+) cells in culture increases fetal hemoglobin production with a concomitant decrease of adult hemoglobin by a post-transcriptional mechanism. SUMMARY: HRI-eIF2αP-ATF4 stress signaling is important not only to inhibit excess globin synthesis during erythropoiesis, but is also critical for adaptation to oxidative stress and for enhancing effective erythropoiesis. Modulation of this signaling pathway with small chemicals may provide a novel therapy for hemoglobinopathy.